Application of the Discovery Learning Model Using Number Adventure Board Props to Improve Elementary School Students' Mathematics Learning Outcomes - Dinda Salsabila Khoirunisa; Aqsha Maulidiyah Putri; Alisyah Dwi Rahmah; Luluk Lailatul Mukarromah; Andika Adinanda Siswoyo; Dino Vita Trisia Bakti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to improve the mathematics learning outcomes of grade II students at SDN Sendang Laok in the addition and vertical subtraction material through the application of the Discovery Learning model, assisted by the Number Adventure Board teaching aid. This research is a Classroom Action Research (CAR) study, based on the Kemmis and McTaggart model, and was carried out in two cycles, including the stages of planning, action implementation, observation, and reflection. The research subjects were 22 grade II students at SDN Sendang Laok in the even semester of the 2025/2026 academic year. Data were collected through learning outcomes tests, observation, and interviews, then analyzed quantitatively and qualitatively. The investigation revealed a significant increase in learning outcomes. The average score of students increased from 10.68 in the pre-test stage with a learning completeness of 0%, to 50 in Cycle I with a completeness of 32%, and reached 84.09 in Cycle II with a classical completeness of 90%. In addition, student activity during learning increased from 35% in Cycle I to 79% in Cycle II. The use of concrete teaching, the use of aids that supported understanding of the concept of place value, the application of Discovery Learning that encouraged active student involvement, and the giving of rewards that increased learning motivation all contributed to this increase in understanding. Thus, the application of the Discovery Learning model, assisted by the Number Adventure Board teaching aid, has been proven effective in improving the mathematics learning outcomes of grade II students in vertical calculation.